THE EFFICACY OF MISOPROSTOL AND SUCRALFATE IN THE THERAPY OF INTESTINAL METAPLASIA - Levent DEMİRTÜRK and Saadeddin HÜLAGÜ and Levent DUMANHAN and Mehmet ALTIN and Mustafa YAYLACI and Ergun UÇMAKLI (Turkish Journal of Gastroenterology, 2020)
-